2023
DOI: 10.3390/admsci13010022
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship Education, a Challenging Learning Process towards Entrepreneurial Competence in Education

Abstract: Entrepreneurship education is a recent field in education. From a field mainly related to small business, it is extended towards enhancement of students’ entrepreneurial attitudes and skills. It can support students in developing an independent and versatile way by growing the spirit of entrepreneurship. Developing entrepreneurship competence among students requires the mastery of concepts by teachers. Training teachers in entrepreneurship education helps them apply specific competences, methods, and tools to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 49 publications
1
18
0
1
Order By: Relevance
“…However, only 13% of the teachers participating in a study by Arruti and Paños-Castro (2023) claimed to support their students in the management of internal and external actors with whom they share achievements and progress. This contrasts with Miço and Cungu (2023 , p. 9), who corroborated that 45.5% of the participants in their study ‘try to create connections and cooperation structures with businesses and community organizations to support the entrepreneurship curriculum in their schools’. It could be why, Sanz Ponce and Núñez Canal (2022 , p. 143) proposed ‘designing achievement tests that actively include the recipients or customers of the products or services made by the students in the entrepreneurial projects, specifically devised for each level of education and educational practice.’…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…However, only 13% of the teachers participating in a study by Arruti and Paños-Castro (2023) claimed to support their students in the management of internal and external actors with whom they share achievements and progress. This contrasts with Miço and Cungu (2023 , p. 9), who corroborated that 45.5% of the participants in their study ‘try to create connections and cooperation structures with businesses and community organizations to support the entrepreneurship curriculum in their schools’. It could be why, Sanz Ponce and Núñez Canal (2022 , p. 143) proposed ‘designing achievement tests that actively include the recipients or customers of the products or services made by the students in the entrepreneurial projects, specifically devised for each level of education and educational practice.’…”
Section: Discussionmentioning
confidence: 61%
“…As Deveci and Seikkula-Leino (2018) stated, there are many studies that advocate including EE in the teacher training curriculum ( Chikodi Ebo et al, 2023 ), and therefore, starting the training in the degree program will enable them to become teachers. In fact, different studies have shown that teachers do not feel sufficiently supported and prepared to implement EE ( Mattila et al, 2009 ; Seikkula-Leino et al, 2010 ; Ruskovaara and Pihkala, 2013 ; Deveci and Seikkula-Leino, 2018 ; Miço and Cungu, 2023 ). In fact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Chen et al (2023) revealed that methods such as business simulations, which are practice-based, are effective in entrepreneurship education. Miço and Cungu (2023) expressed the need to embrace non-traditional teaching and learning methods to develop entrepreneurial competences among students. Similar sentiments are echoed in other similar studies such as Neck et al (2014), Mann et al (2021, Koropogui et al (2024), Motta and Galina (2023), among others.…”
Section: Literature Reviewmentioning
confidence: 99%